Genome-wide CNV analysis reveals variants associated with high-altitude adaptation and meat traits in Qaidam cattle - Shaoke Guo (Elsevier, 2021)
Background: Qaidam cattle are local breeds that habitats in northwest China. It has many excellent characteristics, such as high cold and roughage tolerance, low oxygen adaptability, and tender meat quality. Copy number variation (CNV) can induce phenotypic changes in animals by a variety of effects, and thus affects the biological functions of the animals. To explore the molecular mechanism of its adaptation to extreme cold weather and muscle fat development, the CNV variations in the genome of three Qaidam cattle were detected by whole-genome sequencing, in this study. Results: A total of 16,743 CNVs and 9498 copy number variable regions (CNVRs) were obtained after the screening, which accounts for 2.18% of the bovine genome. The CNVR length detected ranged from 0.3 KB to 10.77 KB, with a total length of 58.17 MB and an average length of 6.12 KB/ CNVR. Through functional enrichment of CNVR related genes, LDHB, and ME1 genes were screened as the key genes for Qaidam cattle to adapt to the cold and low oxygen environments, whereas KIT and FGF18 genes might be related to the coat color and growth. In the CNVR overlapped with QTLs, variation in CAPN1 and CAST genes might be closely related to the tender meat quality of Qaidam cattle. Conclusions: Therefore, this study provides new genetic insights on the environmental adaptability and important economic traits of Qaidam cattle.How to cite: Guo S, Wu X, Pei J, et al. Genome-wide CNV analysis reveals variants associated with high-altitude adaptation and meat traits in Qaidam cattle. Electron J Biotechnol 2021;54. https://doi.org/10.1016/j.ejbt.2021.07.006